Analisis Biaya Transportasi Umum Menggunakan Konsep Perbandingan Biaya Operasional antara Penggunaan Ojek Online dan Ojek Konvensional (Indonesian Journal of Civil Engineering Study, 2025)
Transportation is a system consisting of infrastructure or facilities and service systems that allow movement throughout the region. The movement of transportation in Indonesia is mostly served by private transportation, while public transportation services tend to decline. As a result of this, several companies began to appear that had the initiative to open a public transportation business in the form of online motorcycle taxis. However, this makes conventional motorcycle taxis start to be abandoned. The analytical method used in this study uses descriptive analysis and discourse analysis using quantitative and qualitative approaches. The data used in this study are primary and secondary data, where with primary data this study can obtain data through interviews and questionnaire results. The purpose of this study was to compare vehicle operating costs (BOK) between online motorcycle taxis and conventional motorcycle taxis. From the results of the study, it was found that the results of the calculation of the BOK for online motorcycle taxis were less than conventional motorcycle taxis, therefore many people switched to using online motorcycle taxis because the prices were more affordable.
Keywords: Conventional Motorcycle Taxis; Infrastructure; Online Motorcycle Taxis; Public Transportation; Vehicle Operating Cost